Types and Skills Required by Successful Entrepreneurs: A Case Study - Chaudhari, Tushar (Journal of Commerce and Trade, 2022)
Entrepreneurs are vital for the socio-economic progress of any country. These are the people who translate resources into something creative and are employment givers. It is found that the success rate for entrepreneurs is very low. The primary reason behind this is that these aspirants lack in skills required to be successful one. On the other hand, it is also necessary to understand the type of entrepreneurs. The ability to take risks, innovation, and technical skills are found significant for successful entrepreneurship. Entrepreneurship is a discipline with a acquaintance base theory. It is an consequence of multifaceted socio-economic, psychological, technological, legal, and other factors. It is a active and perilous process. It combines financial resources, technological innovation, and human talent. Entrepreneurship is correspondingly valid to big and small businesses, and to economic and noneconomic activities. In this research paper, the researcher has given a brief description of the term entrepreneurship. He also stated the types of entrepreneurs and skills required for successful entrepreneurs. This research is a qualitative one and is entirely depend upon literature survey.